A low temperature pyrolytic route to amorphous quasi-hexagonal boron nitride from hydrogen rich (NH4)3Mg(BH4)5. Issue 2 (10th December 2019) - Wegner, Wojciech; Fijalkowski, Karol J.; Grochala, Wojciech
Abstract : Amorphous quasi-hexagonal BN with minute amounts of quasi-cubic form was obtained via thermal decomposition of a novel precursor, (NH4 )3 Mg(BH4 )5, at 220–250 °C, which is significantly lower than 1000–1500 °C applied in industrial approaches. Abstract : Pure amorphous quasi-hexagonal boron nitride with minute amounts of amorphous quasi-cubic form was obtained via thermal decomposition of a novel tri-ammonium magnesium penta-borohydride precursor, (NH4 )3 Mg(BH4 )5, in the temperature range of 220–250 °C, which is significantly lower than 1000–1500 °C applied in industrial approaches. The (NH4 )3 Mg(BH4 )5 precursor, the most hydrogen rich mixed-cation borohydride salt known to date (21 wt% H), was prepared via low temperature high-energy dry disc-milling. The compound adopts a tetragonal I 4/ mcm unit cell isostructural with Rb3 Mg(BH4 )5 and Cs3 Mg(BH4 )5 . The multi-step thermal decomposition yields hydrogen contaminated with B2 H6 and borazine volatiles. The solid residue rinsed with water corresponds to amorphous boron nitride of high purity as evidenced by 11 B MAS NMR, PXRD, FTIR and EDX analyses.